Trends in Nutrient Content of Children's Menu Items in U.S. Chain Restaurants - Moran, Alyssa J. (Am J Prev Med, 2017)
INTRODUCTION: Restaurant food is widely consumed by children and is associated with poor diet quality. Although many restaurants have made voluntary commitments to improve the nutritional quality of children's menus, it is unclear whether this has led to meaningful changes. METHODS: Nutrients in children's menu items (n=4,016) from 45 chain restaurants were extracted from the nutrition information database MenuStat. Bootstrapped mixed linear models estimated changes in mean calories, saturated fat, and sodium in children's menu items between 2012 and 2013, 2014, and 2015. Changes in nutrient content of these items over time were compared among restaurants participating in the Kids LiveWell initiative and non-participating restaurants. Types of available children's beverages were also examined. Data were analyzed in 2016. RESULTS: There was a significant increase in mean beverage calories from 2012 to 2013 (6, 95% CI=0.8, 10.6) and from 2012 to 2014 (11, 95% CI=3.7, 18.3), but no change between 2012 and 2015, and no differences in nutrient content of other items over time. Restaurants participating in Kids LiveWell reduced entrée calories between 2012 and 2013 (−24, 95% CI= −40.4, −7.2) and between 2012 and 2014 (−40, 95% CI= −68.1, −11.4) and increased side dish calories between 2012 and 2015 (49, 95% CI=4.6, 92.7) versus non-participating restaurants. Sugar-sweetened beverages consistently constituted 80% of children's beverages, with soda declining and flavored milks increasing between 2012 and 2015. CONCLUSIONS: Results suggest little progress toward improving nutrition in children's menu items. Efforts are needed to engage restaurants in offering healthful children's meals.